ANALISIS PROFITABILITAS, LIKUIDITAS DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN SUBSEKTOR KONSTRUKSI DAN BANGUNAN DI BEI PERIODE 2020–2024 - Ayu Isna Fauziah; Linda Ayu Oktoriza; Ariati Anomsari; Almira Santi Samasta (LPPM STIE Muhammadiah Bandung, 2026)
The study aims to examine how profitability, liquidity, and company size affect the value of companies in the construction and building sub-sector listed on the Indonesia Stock Exchange (IDX) for 2020–2024. The role of company value is very important because it reflects investors' perceptions of the company's performance and prospects. An explanatory quantitative approach was used, supplemented by secondary data, particularly annual financial reports. Profitability is measured using ROE, liquidity using CR, company size using the natural logarithm of total assets, and company value using PBV. Panel data regression with EViews is used for data analysis. The results show that profitability has a significant negative effect on company value, liquidity has a significant positive effect, while company size has a significant negative effect. This means that an increase in profit or company size does not necessarily lead to an increase in company value, while good liquidity management actually increases investor confidence. Overall, all three have a significant effect on company value. Therefore, management is advised to pay attention to operational efficiency and liquidity management, as well as to assess company size strategically. Investors are advised to pay attention to liquidity as a crucial benchmark for making investment decisions. This research contributes empirically to the literature on financial management and the construction sector.